(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
System-based anatomy teaching has gained increasing attention in modern medical education as an effective approach to organizing and delivering anatomical knowledge. Unlike traditional region-based instruction, system-based anatomy emphasizes the integrated study of organs and structures according to physiological systems, facilitating a more coherent understanding of the human body. This article examines the importance of system-based anatomy teaching in improving medical students’ anatomical knowledge and the development of clinical thinking. The study is based on an analysis of contemporary educational literature and pedagogical models used in medical curricula. The findings suggest that system-based anatomy teaching enhances conceptual understanding, supports the integration of anatomy with physiology and pathology, and promotes clinically relevant reasoning. By aligning anatomical education with clinical disciplines, this approach contributes to improved knowledge retention and better preparation of students for clinical practice. System-based anatomy teaching is therefore considered a valuable strategy for optimizing anatomy education in medical universities.